Efektivitas Mediasi Sebagai Alternatif Penyelesaian Sengketa Kredit Pebankan : Studi Putusan Nomor 15/Pdt.G/2025/Pn Pyh - Naily Khairina; Fuad Luthfi (Interdisciplinary Explorations in Research Journal, 2026)
This article analyzes the effectiveness of mediation as an alternative dispute resolution mechanism in banking credit disputes through the study of Decision Number 15/Pdt.G/2025/PN Pyh. The research employs a normative juridical method using statutory, conceptual, and case approaches. The findings indicate that mediation is an effective mechanism in resolving banking credit disputes because it provides opportunities for the parties to reach mutually beneficial agreements, reduces litigation costs, shortens dispute resolution time, and maintains business relationships between creditors and debtors. The settlement agreement resulting from mediation and ratified by the court through a settlement deed has binding legal force and executorial power equivalent to a final court judgment. The study concludes that mediation serves as an efficient and fair alternative for resolving banking credit disputes while promoting legal certainty and justice for the parties involved.